ON THE APPLICATION OF INNOVATIVE TECHNOLOGIES IN PREPARING FUTURE SOCIAL WORKERS - Петренко, Т. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article considers the actual problem is the use of innovative technologies during the educational process of higher educational institutions in the training of future social workers